2016
DOI: 10.1162/leon_a_00924
|View full text |Cite
|
Sign up to set email alerts
|

danceroom Spectroscopy: At the Frontiers of Physics, Performance, Interactive Art and Technology

Abstract: danceroom Spectroscopy is an interactive audiovisual art installation and performance system driven by rigorous algorithms commonly used to simulate and analyze nanoscale atomic dynamics. danceroom Spectroscopy interprets humans as “energy landscapes,” resulting in an interactive system in which human energy fields are embedded within a simulation of thousands of atoms. Users are able to sculpt the atomic dynamics using their movements and experience their interactions visually and sonically in real time. danc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…At its core, however, Narupa is a rigorous scientific simulation environment, with three key emphases: (1) the integration of real-time simulation methodologies into our interaction framework, enabling participants to manipulate and 'feel' the dynamical responses of molecular systems; (2) the ability to make the VR experience one in which facilitates communication, by enabling multiple participants to cohabit the same virtual world together, either together in the same room, or distributed remotely; and (3) active engagement with designers, artists, and human-computer interaction (HCI) experts, in order to create a framework which not only has scientific utility, but which is aesthetically compelling. 5,7,42 This latter point is particularly important given the level of immersion which can be achieved in VR environments. An unattractive aesthetic makes participants unlikely to utilize immersive tools.…”
Section: -39mentioning
confidence: 99%
See 1 more Smart Citation
“…At its core, however, Narupa is a rigorous scientific simulation environment, with three key emphases: (1) the integration of real-time simulation methodologies into our interaction framework, enabling participants to manipulate and 'feel' the dynamical responses of molecular systems; (2) the ability to make the VR experience one in which facilitates communication, by enabling multiple participants to cohabit the same virtual world together, either together in the same room, or distributed remotely; and (3) active engagement with designers, artists, and human-computer interaction (HCI) experts, in order to create a framework which not only has scientific utility, but which is aesthetically compelling. 5,7,42 This latter point is particularly important given the level of immersion which can be achieved in VR environments. An unattractive aesthetic makes participants unlikely to utilize immersive tools.…”
Section: -39mentioning
confidence: 99%
“…Over the past several years, our laboratory has been carrying out an interdisciplinary research program exploring interactive molecular dynamics (iMD) beyond standard 2d interfaces, designed to enable direct multisensory interaction with molecular simulations. [4][5][6][7][8][9] The recent emergence of robust and affordable virtual reality (VR) technologies has been a key enabler in these efforts, allowing us to develop a framework where scientists can manipulate rigorous real-time simulations of molecular systems, as shown in Figure 1 and Video 1 (vimeo.com/244670465). Figure 1 shows two optically tracked participants (each wearing a VR headmounted display (HMD) and holding in each hand wireless controllers which function as atomic 'tweezers') manipulating the real-time MD of a C60 molecule using interactive molecular dynamics in virtual reality (iMD-VR).…”
Section: Introductionmentioning
confidence: 99%
“…240 Different studies demonstrated the possible benefits of immersive and interactive approaches in education, [241][242][243][244] and multiple virtual reality frameworks were designed for simultaneous immersion of multiple persons, allowing for collaborative environments. 192,[245][246][247][248][249]…”
Section: Interactive Approaches In Classical Simulationsmentioning
confidence: 99%
“…First, PETRI was connected to control a recreation of Dawkins' Blind Watchmaker program: the canonical IEC example for evolving creature like images called biomorphs [4]. Second, the interface was adapted to control a system called danceroom Spectroscopy, an immersive and interactive atomic simulation allowing participants to explore quantum phenomena through movement and dance [17,7].…”
Section: Applicationsmentioning
confidence: 99%